Collision and grounding of ships and offshore structures : proceedings of the 6th International Conference on Collision and Grounding of Ships and Offshore Structures, ICCGS, Trondheim, Norway, 17-19 June 2013 /: proceedings of the 6th International Conference on Collision and Grounding of Ships and Offshore Structures, ICCGS, Trondheim, Norway, 17-19 June 2013. (©2013) - Unknown
No abstract available